The Si D'nOK Application as a Catalyst for Bureaucratic Reform Based on E-Government in Achieving Good Governance in Semarang City - Alifia Dyah Prameshwari Utami (Faculty of Law, Universitas Negeri Semarang, 2025)
In today's digital era, the development of public service systems that can be accessed remotely online is essential. This system development serves as one of the strategic solutions the government can implement to achieve Good Governance. Through e-government-based bureaucratic reform, government administration is expected to become more effective, efficient, and transparent. The Si D’nOK application, developed by the Population and Civil Registration Office (Dispendukcapil) of Semarang City, is designed to facilitate digital access to civil administrative services. This study aims to analyze the Si D’nOK application as a catalyst for e-government-based bureaucratic reform in realizing good governance in Semarang City, with reference to the Mayor of Semarang Regulation Number 27 of 2021 concerning the Implementation of Electronic-Based Government Systems (SPBE) within the Semarang City Government. The study explores the implementation of the Si D’nOK application, its role in bureaucratic reform, and the supporting and inhibiting factors affecting its use. A qualitative approach was applied in this research, with data collected through interviews, literature reviews, and documentation. The research findings indicate that the Semarang City Population and Civil Registration Office (DISPENDUKCAPIL) has implemented policies related to the Si D’nOK application by monitoring the system. However, many members of the public still experience difficulties and are not yet accustomed to using the Si D’nOK application. To address this issue, broader and more comprehensive outreach is needed, especially targeting the elderly. Additionally, the recruitment of more technical experts is necessary to support the more effective operation of the Si D’nOK application so that documents can be processed promptly, preventing delays in service delivery.